WORKSHOP KURIKULUM PENDIDIKAN NON FORMAL DENGAN MENELAAH STANDAR ISI DAN STANDAR PROSES - sb, eka pasca (Kopertis Wilayah X (Sumbar, Riau, Jambi, dan Riau Kepulauan), 2017)
ABSTRACT Non-Formal Education one of which is equality education Package B Equivalent SMP. During PKBM Kasih Bundo not designed study with reference to credit units of competence (SKK), so there is no integration between content standards with the standards in the implementation process. The purpose of this research is to improve the competence of tutors in designing the curriculum devoted to the annual program and the semester program by examining the content standard and the standard of non-formal education process through workshops. This type of research is descriptive kualitati where the research will be described without altering the information obtained during the study berlangsung.data obtained is the data during the workshop using triangulation. The result showed that the first phase of the workshop were able to increase the ability of tutors in the preparation of the annual program and the semester program at SKK charted in the form of face to face, tutorials, and independent.